Welfare perceptions of public expenditure on environmental and non-environmental goods - Ong, Qiyan (2020)
Increasing research shows that income growth has a less than substantial impact on people’s well-being. In contrast, environmental factors are found to have non-negligible impact on people’s well-being. The research raises the question of whether more can be done to improve the wellbeing of the public through government spending on the environment. We conducted pair comparison surveys using the variance stable rank method on preferences for public expenditure on education, environment and transportation in Singapore. Both aggregate preference rankings as well as rank ordered logitregression analysis on individuals’ rankings reveal that respondents perceive larger improvements in well-being from increasing public expenditure on environment goods compared to an equivalent increase in public expenditure on education goods.